Dispositional Mindfulness, Perceived Stress, and Mental Well-Being in the Cancer Survivorship - Xiaoyan Liu; Pei Hwa Goh; Wei Xu; Jingjing Zhang (International Journal of Psychotherapy Practice and Research, 2019)
The present study aims to investigate how dispositional mindfulness affects the mental well-being of cancer patients through the way they perceive stress. A total of 182 moderate and advanced gastrointestinal cancer patients volunteered to complete the Mindful Attention Awareness Scale (MAAS), the Chinese Perceived Stress Scale (CPSS), and the General Health Questionnaire (GHQ). Results showed that perceived stress significantly mediated the relationship between dispositional mindfulness and all dimensions of the mental well-being as captured by the GHQ (i.e. anxiety/depression, social dysfunction, and loss of confidence), and perceived stress was positively correlated with all the dimensions of mental well-being. Results of the Structural Equation Model showed that the model fit the data very well (χ2/df = 1.72，RMSEA = 0.063 (95% CI = 0.014 0.103), CFI = 0.984, TLI = 0.970, SRMR=0.041). Further analyses showed that dispositional mindfulness predicted all the dimensions of psychological well-being. Specifically, higher levels of dispositional mindfulness predicted reduced subjective perceptions of stress, which in turn predicted lower levels of anxiety/depression, social impairment, and loss of confidence. This study indicated a possible mechanism of intervention focused on improving mindfulness capability. Future work is encouraged to investigate the long-term influence of dispositional mindfulness on perceived stress and psychological well-being in cancer patients with other types of cancer.
Keywords: Gastrointestinal Cancer